Tasawuf Tanpa Tarekat: Pengalaman Turki dan Indonesia - Akhmad Rizqon Khamami (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2016)
This article seeks to display a development of sufi without t}arîqah in two countries, namely Turkey and Indonesia. In spite of the banning of sufi orders in Turkey, hitherto Sufism lingers in the Republic. Several sufi orders work in silent, but they do make contribution on the socio-political sphere of Turkey. On the other side, some Turkish sufi practitioners transform themselves into sufi without ?arîqah as an adaptation to the secular state’s strict policy on religion, such those as Bediuzzaman Said Nursi dan Fethullah Gülen. In Indonesia, Sufism has arisen conspicuo-usly among the Salafi after for some times being lied down due to an accusation of being the source for backwardness of Muslim community. In turn, it is that sufi without ?arîqah eventually take shape. Due to differing on socio-political condition and on intellectual debates of the both countries, the sufi without ?arîqah leads to different ways in respective country. While Turkish sufi without ?arîqah turn out to be a movement taking part in secular Turkey, sufi without ?arîqah in Indonesia—particularly that of Salafi—tends to be a mode of self-entertaining for the sake of religious sensation.